Evaluación del desempeño financiero de una empresa familiar dedicada a la metalmecánica (2018)
In Colombia the family business is the most common commercial organization, constituted to generate wealth and autonomy to the business family and as a consequence to the society in which it is present. Being these, a complex and unique organization by the culture that the family business printed on it. A financial study allows to know and understand the current situation of the organizations and why it went over there. Therefore, for the present study of the financial performance of the family business dedicated to the metal mechanical in the livestock-poultry sector the financial and organizational aspects are taken into account.